Utilization of Electrolyte Solution in Nanotube Formation on Ti-6Al-4V Metal Alloy - Charlena Charlena; Tetty Kemala; Armi Wulanawati (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
Formation of nanotube morphology on the surface of Ti-6Al-4V metal did not occur homogeneously, so when it was coated with hydroxyapatite, it did not merge well. One of the factor that affected the inhomogeneously formed nanotube was the utilization of electrolyte solution. The research has been done to observe the effect of electrolyte solution in the formation of nanotube morphology on the surface of Ti-6Al-4V metal alloy. Electrolyte solution that was used was ethylene glycol, HF, and NH4F with time variation of an hour, 2 hour, and 3 hour. Formation of nanotube morphology on the surface of Ti-6Al-4V metal alloy was done using anodization process. The result showed that in HF electrolyte solution which was anodized for an hour ɑ and β phase that composed Ti-6Al-4V metal alloy was formed, meanwhile when using electrolyte solution of ethylene glycol + NH4F for 2 hours showed that there were pores that opened on Ti-6Al-4V metal alloy surface. Nanotube morphology on the surface of Ti-6Al-4V metal alloy was formed using electrolyte solution of ethylene glycol + NH4F which was anodized for 3 hours.